PENGEMBANGAN DIOSIR (DIORAMA SIKLUS AIR) BERBASIS AUGMENTED REALITY UNTUK MENINGKATKAN MOTIVASI BELAJAR (SISWA KELAS V SDN SLOROK 1 GARUM KABUPATEN BLITAR) - Zahroin, Nurina; Tri Oktaviani, Ragil; Wafa, Khoirul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Thist study aims to develop a learning media called DIOSIR (Water Cycle Diorama) based on Augmented Reality to enhance the learning motivation of fifth-gradet elementaryt school studentst. The researcht approacht used ist Researcht and Developmentt (R&Dt), following the development steps of the Borg and Gall model. Datat weret collectedt usingt four mtethodst: interviewst, observationst, questionnairest, and documentationt. The resultst showedt thatt the media received a validity score of 92% from media experts and 90% from content experts, both of which fall into the